Estrogen increases proteasome activity in murine microglial cells - Reed, Janelle L; Dimayuga, Filomena O; Davies, Laurie M; Keller, Jeffrey N; Bruce-Keller, Annadora J (Neuroscience letters, 2004)
During inflammation, microglial cells go through phenotypic and functional changes that include the production and release of large amounts of oxygen and nitrogen radicals. As such, activated microglia are subject to heightened oxidative stress. The multicatalytic proteasome clears oxidized and damaged proteins from cells, and has been shown to be an important aspect of the microglial compensatory response to activation. The female sex steroid estrogen is both cytoprotective and anti-inflammatory, and has been shown to affect microglial signaling in particular. To determine if estrogen might affect the proteasome in microglial cells, we examined the effects of 17β-estradiol treatment on proteasome activity in N9 microglial cells. Specifically, we measured ATP-dependent and ATP-independent chymotrypsin-like, trypsin-like, and peptidyl glutamyl peptide hydrolase (PGPH)-like activities in response to both 17β-estradiol and interferon gamma. Data indicate that estrogen, but not interferon gamma, significantly increases ATP-dependent chymotrypsin-like and PGPH-like activity. Furthermore, this effect was blocked by the p44/42 MAPK inhibitor PD98059. Hence, these data demonstrate that through the MAPK pathway, estrogen can upregulate proteasome activity, suggesting a possible mechanism for estrogen’s cytoprotective effects.